Analisis Motivasi Belajar Mahasiswa Biologi pada Perkuliahan Online Semester Genap Tahun Akademik 2020/2021 - Tewololon, Veronika Bulu; Samsuri, Taufik; Muliadi, Agus (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine the learning motivation of Biology students in online lectures in the even semester academic year 2020/2021. The type of research used is descriptive research. The resrarch sample is Biology student. The data collection method used in this study is a questionnaire which was tested on 20 respondents. Indicator of learning motivation are diligent in facing tasks, tenacious in the facae of difficulties, showing interest, happy to work independently, able to defend opinions, not easy to let go of things they believe in, happy to find and solve problem questions. Data on the result of Biology students’ learning motivation was collected using a questionnaire sheet. The data collected were analysed. Leraning motivation results are based on the following categories: 80-100 highly motivated, 51-80 motivated, 31-50 moderately motivated, 10-30 less motivated. Based on the research results obtained as a whole, biology students have a motivation score of 84,15 and an average score of 4 with a highly motived category, but the most prominent in this assessment is being diligent in facing assignments, namely 4,42 and the lowest being happy to find and solve problem, nemaly 0,22. Therefore, it can be seen that motivation has a very important role in the learning process, that’s why it is expected to remain motivated so that is the goal of learning can be achieved optimally.